Effect of DEA in Membrane Gas Absorption System Using Polymeric Flat Sheet Membrane - Ahmad, A. L.; Sunarti, A. R.; Lee, K. T.; Fernando, W. J. N. (Journal of Applied Membrane Science & Technology, 2017)
The objective of this study was to investigate the potential process of the removal of carbon dioxide (CO2) from flue gases by using developed membrane gas absorption system. The experiments were performed in membrane gas absorption system consisted 0.45 Î¼m pore size microporous polyvinylidenefluoride (PVDF) flat sheet membrane. Diethanolamine (DEA) solution was employed as the liquid absorbent. The operating parameters such as the gas and liquid flow rate were setup at 100 cm3/min and 25 cm3/min and liquid absorbent was at room temperature. The effect of DEA concentration was studied with variation in range 1 M to 5 M. In addition, the experiments were carried out with 20%, 40% and 100% gas ratio CO2Â to N2. The results show that hydrophobic polymeric membranes such as PVDF can be efficiently used for gas absorption with optimized concentration of DEA.